1975
DOI: 10.1039/f19757102468
|View full text |Cite
|
Sign up to set email alerts
|

Tin oxide surfaces. Part 3.—Infrared study of the adsorption of some small organic molecules on tin(IV) oxide

Abstract: The tin@) oxide surface is strongly oxidising towards smaI1, reactive organic molecules. Methanol is chemisorbed to give methoxy groups but these are readily oxidised to a surface formate at temperatures >320 K. Acetone and acetaldehyde are adsorbed predominantly as acetates but some evidence is found for an en01 form which may be responsible for the rapid deuterium exchange between hexadeuteroacetone and surface hydroxyl groups. The spectra of the formate and acetate structures are confirmed by adsorption of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 0 publications
4
29
0
Order By: Relevance
“…Condensation reactions of acetone are catalyzed by acids as well as by bases. Acetate has also been observed after adsorption of acetone or acetaldehyde on Sn0 2 [731]. The authors ascribed this to oxidation of the reagents by the oxide; however, it seems very likely that the reaction was analogous to that observed on alumina with acetone, and that acetaldehyde underwent a Cannizzaro disproportionation, a typical reaction of aldehydes in alkaline media.…”
Section: Modification Of Metal Oxide Surfacesmentioning
confidence: 86%
See 2 more Smart Citations
“…Condensation reactions of acetone are catalyzed by acids as well as by bases. Acetate has also been observed after adsorption of acetone or acetaldehyde on Sn0 2 [731]. The authors ascribed this to oxidation of the reagents by the oxide; however, it seems very likely that the reaction was analogous to that observed on alumina with acetone, and that acetaldehyde underwent a Cannizzaro disproportionation, a typical reaction of aldehydes in alkaline media.…”
Section: Modification Of Metal Oxide Surfacesmentioning
confidence: 86%
“…The carboxylate ions are easily recognized by the strong infrared absorption for symmetric and asymmetric stretching vibrations [8,9,14,15]. CarhL>xylate ions which have been first observed on alumina were found also on Sn0 2 [731] and on Fe 2 0 3 [745][746][747].…”
Section: Modification Of Metal Oxide Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…The vesicle fraction fluoresced at 515 nm when irradiated at 370 nm. [10] Although the catalytic activity of MgO is lower than other more basic solids, such as heavier alkaline earth oxides [1] or aluminum phosphorous oxinitrides catalysts, [2] its well-known structure makes it suitable for mechanistic studies. [3] In fact, the acetone ± MgO system has been the subject of several infrared and temperature-programmed desorption studies, H exchange experiments have also been reported.…”
mentioning
confidence: 99%
“…It is reported that the adsorption of water on the oxide surface results in the formation of molecular water at low temperature and hydroxyl groups at high temperature. (36,37) Therefore, the decrease in resistance of all films with decreasing temperature below 100°C can be ascribed to the adsorption of molecular water. Figure 7 shows the temperature dependence of the sensitivity of TiO 2 films deposited under three different pressures.…”
Section: Resultsmentioning
confidence: 99%